Measuring grit, self-efficacy, curiosity, and intolerance of uncertainty in first-generation college and first-generation osteopathic medical students - DeWitt Jones; Monet McCalla; Elizabeth A. Beverly (BMC Medical Education, 2023)
Abstract Background Medical school is a challenging time, with many medical students reporting symptoms of burnout, depression, anxiety, suicidal ideation, and psychological distress during pre-clinical and clinical years. First-generation college and first-generation medical students may be two groups of students at increased risk for the negative psychosocial effects of medical school. Importantly, grit, self-efficacy, and curiosity are protective factors against the negative psychosocial effects of medical school, whereas intolerance of uncertainty is a risk factor. Thus, research examining the associations among grit, self-efficacy, curiosity, and intolerance of uncertainty in first-generation college and first-generation medical students is needed. Methods We conducted a cross-sectional, descriptive study to assess medical students’ grit, self-efficacy, curiosity, and intolerance of uncertainty. We conducted independent samples t-tests and regression analyses using SPSS statistical software version 28.0. Results A total of 420 students participated in the study for a response rate of 51.5%. One-fifth of participants (21.2%, n = 89) identified as first-generation students, 38.6% (n = 162) participants reporting having a physician relative, and 16.2% (n = 68) reported having a physician parent. Grit, self-efficacy, and curiosity and exploration scores did not differ by first-generation college status, physician relative(s), or physician parent(s). However, total intolerance of uncertainty scores differed by physician relative(s) (t= -2.830, p = 0.005), but not by first-generation status, or physician parent(s). Further, subscale scores for prospective intolerance of uncertainty differed by physician relative(s) (t= -3.379, p = 0.001) and physician parent(s) (t= -2.077, p = 0.038), but not by first-generation college student status. In the hierarchical regression models, first-generation college student status and first-generation medical student status were not predictive of grit, self-efficacy, curiosity and exploration, or intolerance of uncertainty, although statistical trends were observed with students with physician relative(s) predicting lower intolerance of uncertainty scores (B= -2.171, t= -2138, p = 0.033) and lower prospective intolerance of uncertainty (B= -1.666, t= -2.689, p = 0.007). Conclusions These findings suggest that first-generation college students did not differ by grit, self-efficacy, curiosity, or intolerance of uncertainty. Similarly, first-generation medical students did not differ by grit, self-efficacy, or curiosity; however, first-generation medical students showed statistical trends in higher total intolerance of uncertainty and higher prospective intolerance of uncertainty. Additional research needs to confirm these findings in first-generation medical students.